Spontaneous droplet generation via surface wetting. Issue 19 (8th September 2020) - Liu, Fengyi; Xu, Teng; Liu, Wenjing; Zheng, Xiaoshan; Xu, Jian; Ma, Bo
Abstract : A surface wetting-driven droplet generation microfluidic chip was developed and produces droplets spontaneously without any power source. Abstract : A surface wetting-driven droplet generation microfluidic chip was developed, and could produce droplets spontaneously once adding a drop of oil and an aqueous sample on the chip without any power source and equipment. The chip is simply composed of three drilled holes connected by a single microchannel. The aqueous sample dropped in the middle hole could be converged and segmented into monodispersed droplets spontaneously by preloading oil in the side hole, and then flow into the other side hole through the microchannel. To address the high throughput and stability in practical applications, a siphon pump was further integrated into the microfluidic chip by simply connecting oil-filled tubing also acting as a collector. In this way, droplets can be generated spontaneously with a high uniformity (CV < 3.5%) and adjustable size (30–80 μm). Higher throughput (280 Hz) and multi-sample emulsification are achieved by parallel integration of a multi-channel structure. Based on that, the microfluidic chip was used as the droplet generator for the ddPCR to absolutely quantify S. mutans DNA. This is the first time that the feasibility of droplet generation driven only by oil wettability on hydrophobic surfaces is demonstrated. It offers great opportunity for self-sufficient and portable W/O droplet generation in biomedical samples, thus holding the potential for point-of-care testing (POCT).